GC-MS ANALYSIS OF PHYTOCOMPONENTS IN THE METHANOLIC EXTRACT OF AZADIRACHTA INDICA (NEEM) - S. BALASUBRAMANIAN,; D.GANESH,; SURYA NARAYANA VVS, (International Journal of Pharma and Bio Sciences, 2014)
Azadirachta indica, is locally called as “Neem” belongs to the family Meliaceae. “Neem” is a medicinal herb traditionally used for the treatment of Diabetes, leprosy and Respiratory diseases. The present study was carried out to identify the phytocomponents present in the methanolic extract of the leaves of Azadirachta indica by GC-MS analysis. From the GC-MS results five compounds were identified as major constituents, they are Phytol, Linolenic acid, Homo-γ-linolenic acid, Palmitic acid and Tridecylic acid.